HARMONISASI NORMA AGAMA ISLAM DALAM SISTEM POLITIK HUKUM DI INDONESIA - M, Sirajuddin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
Harmonization of Islamic Religious Norm in the System of Political Law in Indonesia. This study is aimedat exploring the relationship between norms of Islam and politics in Indonesia as well as the harmonization ofnorms of religion in the political system of law in Indonesia. The type of this research is a law’s research (legalresearch) that uses descriptive-normative approach, while the framework of the theory is to use the politicalsystem of law. The relationship between politics and religion is a region that is diferensiatif, not integral orseparate region.The political system of law in Indonesia providessome spaces for change and absorption with thereligious norms, including norms of Islam, to be a source of legal legislation in national and local area. Therefore,the philosophy and ideology of Pancasila as still able to answer the growing and dynamic development of thepresent era. One is the answer to the deliberative democratic system that developed last decade that not onlypromote the most votes, but who sought is common ground to build togetherness and cooperation